1997
DOI: 10.1007/bf03217322
|View full text |Cite
|
Sign up to set email alerts
|

Equity, empowerment and different ways of knowing

Abstract: This paper considers the experiences of two sets of students who attended schools that taught mathematics in completely different ways. One of the schools used a traditional, textbook approach, and the other used an open, project-based approach. The latter approach produced equity between girls and boys whereas the textbook approach prompted many of the girls to under achieve. This paper will consider the experiences of girls and boys who followed the project-based approach, reflect upon the sources of equity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 9 publications
1
36
0
3
Order By: Relevance
“…We wonder if this means that, once boys have one method they are satisfied with, they choose to ignore any other possibilities. This is consistent with Boaler's (1997) finding that girls were more concerned with the connectedness of their knowing and the links between ideas, whereas boys tended to take a more 'separate' approach which valued certainty, absolute truth, procedures and algorithms.…”
Section: Discussionsupporting
confidence: 86%
“…We wonder if this means that, once boys have one method they are satisfied with, they choose to ignore any other possibilities. This is consistent with Boaler's (1997) finding that girls were more concerned with the connectedness of their knowing and the links between ideas, whereas boys tended to take a more 'separate' approach which valued certainty, absolute truth, procedures and algorithms.…”
Section: Discussionsupporting
confidence: 86%
“…The results obtained in this small-scale case study resonate with the findings reported in the large body of empirical research that indicates how collaborative learning experiences positively impact upon girls' affective responses to mathematics. For example , Boaler (1997a;b;, Barnes (2000) and Anderson (2005) all confirm the benefits of collaboration in promoting girls' enjoyment of mathematics. The affective advantages of cognitive-activation approaches to mathematics instruction have also been documented (OECD, 2016) and, in line with our findings, it therefore seems plausible that the concept of collaborative cognitiveactivation holds promise for improving girls' attitudes to mathematics.…”
Section: Discussionmentioning
confidence: 92%
“…The learning environment could under specific conditions create a new type of agency for the students, which imply different division of labour between teacher and students (Boaler and Greeno, 2000;Hakkarainen, Lipponen and Järvelä, 2001). The examples we have shown in this paper give suggestions of types of interactions in which the students have possibilities to develop conceptual knowledge, since they are engaged in a conceptual type of talk.…”
Section: Discussionmentioning
confidence: 99%